Global health diplomacy at the intersection of trade and health in the COVID-19 era - Vijay Kumar Chattu; Shalini Pooransingh; Hamid Allahverdipour (Tabriz University of Medical Sciences, 2021)
Global health diplomacy has gained significant importance and undoubtedly remained high on the agendas of many nations, regional and global platforms amid the coronavirus disease 2019 (COVID-19) pandemic. Many countries have realized the importance of the health sector and the value of a healthy workforce. However, there is little control on issues related to trade that impact on human health due to the dominance of profit-oriented business lobbies. A balance, however, needs to be struck between economic profits and a healthy global population. This paper aimed to highlight the importance of building capacity in global health diplomacy, especially during the COVID-19 pandemic so that health personnel may effectively negotiate on the multisectoral stage to secure the resources they need. The recent proposal to waive off certain provisions of the Trade-Related Aspects of Intellectual Property Rights (TRIPS) agreement for the prevention, containment and treatment of COVID-19 by India and South Africa at the World Trade Organization (WTO) presents an important opportunity for all governments to unite and stand up for public health, global solidarity, and equitable access at the international level so that both developed and developing nations may enjoy improved health outcomes related to the COVID-19 pandemic.